A Hidden Complication of Pigtail Catheter Insertion - Garcia de Alencar, Júlio C. (Clin Pract Cases Emerg Med, 2020)
Pigtail catheters have emerged as an effective and less morbid alternative to traditional chest tubes for evacuation of pleural air. Rare complications in the literature have been reported. We report a case of a 92-year-old male who presented with dyspnea and shock, noted to have a pneumothorax requiring tube thoracostomy. Computed tomography demonstrated pigtail within the lung parenchyma. We discuss the implications of this occurrence.